2012
DOI: 10.1100/2012/697201
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Biocompatibility of Chitosan and Silk Fibroin Blend Films for Application in Skin Tissue Engineering

Abstract: Chitosan/silk fibroin (CS/SF) blend films were prepared and evaluated for feasibility of using the films as biomaterial for skin tissue engineering application. Fourier transform infrared spectroscopy and differential scanning calorimetry analysis indicated chemical interaction between chitosan and fibroin. Chitosan enhanced β-sheet conformation of fibroin and resulted in shifting of thermal degradation of the films. Flexibility, swelling index, and enzyme degradation were also increased by the chitosan conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 44 publications
2
56
0
1
Order By: Relevance
“…The amide II band is divided into two peaks at 1514 and 1541 cm −1 confirming, therefore, that the composite contains both random coil and β sheet structures. The new peak appearing at 1260 cm −1 presented conformation transition from random coil to β-sheet of SF (Luangbudnark et al 2012). These results lead to the fact that in addition to the chitosan role in protecting silver nanoparticles from agglomeration by enveloping them, it can also increase the transition from random coil to beta sheet of SF.…”
Section: Discussionmentioning
confidence: 99%
“…The amide II band is divided into two peaks at 1514 and 1541 cm −1 confirming, therefore, that the composite contains both random coil and β sheet structures. The new peak appearing at 1260 cm −1 presented conformation transition from random coil to β-sheet of SF (Luangbudnark et al 2012). These results lead to the fact that in addition to the chitosan role in protecting silver nanoparticles from agglomeration by enveloping them, it can also increase the transition from random coil to beta sheet of SF.…”
Section: Discussionmentioning
confidence: 99%
“…At 60% compressive strain level, all prepared scaffolds in this study showed >10 MPa strength with similar porosity (>72%). Pure SF, especially in dry state, lacks structural stability . PVA blending gives the desired mechanical integrity in these scaffolds to bear the load of human body.…”
Section: Discussionmentioning
confidence: 97%
“…Higher absorption and permeability on body exudation could improve the healing of diabetic cutaneous wound. 29 Furthermore, chitosan has been described as being delivered in controlled protein release devices based on its cationic nature. An ionic complex can be formed between chitosan and growth factors, and these stable but reversible interactions can protect bioactive factors from infiltrating the surrounding environments.…”
Section: Discussionmentioning
confidence: 99%